Appraisal of Indoor Microbial Pollutants at University Research Labs and Offices under Mediterranean Climate. Issue 1 (June 2020) - Abed, E Y; Madhoun, W A; Elmanama, A A; Kim, H; Xu, X; Ros, F C
Abstract: Bacteria and fungi grow indoors when sufficient moisture is available. This study aims to determine the total viable bacterial count and fungi levels and to compare these levels among various science teaching laboratories and staff offices in Gaza city universities. A cross-sectional prospective study was conducted, sixty-five (65) air samples were collected from three local universities using Air Sampler. Auto Ranging Multimeter was used to record humidity and temperature. Air samples with counts of bacteria or fungi more than 500 Colony forming units "CFU"/m 3 were considered polluted according to the world health organization (WHO) standards. Among the 65 samples from the three universities, 48 sample (73.8%) had more than 500 colonies/100L. In term of fungal concentration, nine samples (13.8%) exceeded the WHO standards of 500 CFU/m 3 . The highest percentage of bacterial load in air samples at the three universities (more than 500 CFU/m 3 ) was at IUG with 80.8% due to its old existence, more labs and lab activities. The lowest was at AQU with 61.5% due to less lab and lab activities. The highest percentage of fungal load in air samples at the three universities also were at IUG with 19.2 % and the lowest was at AQU with 7.7%.